Embedding CsPbBr3 quantum dots into a pillar[5]arene-based supramolecular self-assembly for an efficient photocatalytic cross-coupling hydrogen evolution reaction. Issue 16 (16th April 2021) - Zhong, Kaipeng; Lu, Siyu; Guo, Wenting; Su, Junxia; Sun, Shihao; Hai, Jun; Chen, Fenjuan; Wang, Aiqin; Wang, Baodui
Abstract : A highly efficient artificial light-harvesting system was successfully fabricated based on the in situ confined growth of CsPbBr3 QDs in a PTY⊃EYB assembly. Abstract : Light-harvesting is a key step in photosynthesis, but it is still a challenge to create an efficient artificial light harvesting system in a broader solar spectrum to mimic natural processes. Here, we have fabricated, for the first time, a highly efficient artificial light-harvesting system through directly embedding CsPbBr3 quantum dots (QDs) inside a supramolecular self-assembly of thymine functionalized-pillar[5]arene (PTY) and an eosin Y-based derivative (EYB). The donor CsPbBr3 QDs exhibit a broad spectral absorption in the UV-visible range, and their emission shows good spectral overlap with the absorption of EYB, thus effective excitation energy is transferred from CsPbBr3 to the acceptor EYB with an energy transfer efficiency of 96.5%. Importantly, the combination displayed excellent photocatalytic activity in cross-coupling hydrogen evolution reactions, and the product yield was more than 2.5 times that obtained using eosin Y alone. Our research opens up a new avenue for utilizing perovskite QDs with broad spectral absorption as the energy donor to construct efficient light-harvesting systems for solar energy conversion.